Assessing pricing, distribution, and warehousing strategies in influencing consumer demand and purchase decisions: Evidence from Indonesia - Ika Pratiwi; Roosganda Elizabeth; Fatari; Basrowi; Uli Wildan Nuryanto (Social Sciences and Humanities Open)
This study investigates the relationships between pricing, distribution, warehousing strategies, consumer demand, and purchase decisions in Indonesia. This study employs a quantitative methodology, including data collected from 160 respondents from 60 companies across various sectors, and explores how these strategies impact consumer demand and purchase decisions. The findings reveal that pricing strategy significantly influences consumer demand and purchase decisions, emphasizing the need for companies to align pricing strategies with market conditions and consumer preferences. Distribution strategy directly affects purchase decisions but not consumer demand, indicating the importance of targeted distribution efforts to drive purchase choices. Warehousing strategy is critical, significantly affecting consumer demand and purchase decisions. Efficient warehousing practices not only ensure product availability but also shape consumer demand. Consumer demand acts as a mediator between pricing strategy and purchase decisions, as well as between warehousing strategy and purchase decisions. It highlights the potential for companies to optimize the impact of these strategies through consumer demand as an intermediary step.